Tumor-induced myeloid-derived suppressor cells promote tumor progression through oxidative metabolism in human colorectal cancer - OuYang, Li-Ying (J Transl Med, 2015)
BACKGROUND: Expansions of myeloid-derived suppressor cells (MDSCs) have been identified in human solid tumors, including colorectal cancer (CRC). However, the nature of these tumor-associated MDSCs and their interactions with tumor cells in CRC are still poorly understood. METHODS: The percentages and phenotype of MDSCs in peripheral blood and tumorous and paraneoplastic tissues from CRC patients, as well as the clinical relevance of these MDSCs, were assessed. Age-matched healthy donors were included as controls. The interaction between MDSCs and T cells or tumor cells was investigated in a coculture system in vitro, and the molecular mechanism of the effect of MDSCs on T cells or tumor cells was evaluated. RESULTS: We discovered that CRC patients had elevated levels of CD33(+)CD11b(+)HLA-DR(−) MDSCs in primary tumor tissues and in peripheral blood, and the elevated circulating MDSCs were correlated with advanced TNM stages and lymph node metastases. Radical resection significantly decreases the proportions of circulating MDSCs and CD4(+)CD25(high)FOXP3(+) regulatory T cells. In vitro, CRC cells mediate the promotion of MDSC induction. Moreover, these tumor-induced MDSCs could suppress T cell proliferation and promote CRC cell growth via cell-to-cell contact. Such effects could be abolished by the inhibition of oxidative metabolism, including the production of nitric oxide (NO), and reactive oxygen species (ROS). CONCLUSIONS: Our results reveal the functional interdependence between MDSCs, T cells and cancer cells in CRC pathogenesis. Understanding the impact of MDSCs on T cells and tumor cells will be helpful to establish an immunotherapeutic strategy in CRC patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-015-0410-7) contains supplementary material, which is available to authorized users.